The content of fears in school children - Jurin, Tanja (Array, 2009)
The aim of this study was to determine the content of fears in school children and its possible association with the age, gender and other characteristics of the child. The study was conducted on a sample of 269 pupils, aged between 10 and 14, from a single elementary school in Zagreb. A questionnaire included the item: “ If you had a magic wand, which of your fears would you like to make disappear?” Children responded to this question with a short written answer. Most frequently, children answered that they would like make their “ fear of school” disappear. In fact, almost one fifth of pupils reported having a fear of school. Fears of evil people, one’ s own death and negative emotions were less commonly represented. Even less prevalent were fears of parents, animals, heights and darkness. Fears of ghosts, catastrophes, nightmares and thunder were the least commonly represented. Although dominant amongst pupils of both genders, girls more frequently reported a fear of school. In addition, girls were also more afraid of dark and failure in comparison to boys. Results further indicated that, with age, fear of school became more prevalent with age. Older boys were more afraid of their parents, animals and evil people (attacks, violence) whilst younger boys were more afraid of their own negative emotions (“ I would like to remove my fear of fear” ) and concerns for their own health. Overall, the results indicate gender and age differences in developmental fears, a finding that clinical psychologists should take into consideration in their therapeutic work.